Cholinesterase Inhibitory Activity of Some Semi-rigid Spiro Heterocycles: POM Analyses and Crystalline Structure of Pharmacophore Site - Hadda, Taibi B.; Talhi, Oualid; Silva, Artur S.M.; Senol, Fatma Sezer; Orhan, Ilkay Erdogan; Rauf, Abdur; Mabkhot, Yahia N.; Bachari, Khaldoun; Warad, Ismail; Farghaly, Thoraya A.; Althagafi, Ismail I.; Mubarak, Mohammad S. (Mini Reviews in Medicinal Chemistry, 2018)
Background: Cholinesterase family consists of two sister enzymes; acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) which hydrolyze acetylcholine. Since deficit of acetylcholine has been evidenced in patients of Alzheimer's disease (AD), cholinesterase inhibitors are currently the most prescribed drugs for the treatment of AD. Objective: our aim in this article was to investigate the inhibitory potential of five known compounds (2-6) with spiro skeleton against AChE and BChE using ELISA microplate assays. In addition to their ChE inhibitory effect, their physico-chemical properties were also calculated. Moreover, the present work aims at investigating the charge/geometrical effect of a hypothetical pharmacophore or bidentate site in a bioactive group, on the inhibition efficiency of spiro compounds 2-6 by using Petra/Osiris/ molinspiration (POM) and X-ray analyses. Method: In the present study, five compounds (2-6) with spiro skeleton have been synthesized and tested in vitro for their inhibitory potential against AChE and BChE using ELISA microtiter plate assays at 25 μg/mL. Results: Results revealed that three of the spiro compounds tested exert more than 50% inhibition against one of cholinesterases. Compound 5 displayed 68.73 ± 4.73% of inhibition toward AChE, whereas compound 6 showed 56.17 ± 0.83% of inhibition toward BChE; these two previously synthesized compounds have been the most active hits. Conclusions: Our data obtained from screening of compounds 2-6 against the two cholinesterases indicate that three of these show good potential to selectively inhibit AChE or BChE. Spiro compounds 2, 5, and 6 exhibited the most potent activity of the series against AChE or BChE with inhibition values in the range 55-70%.
Keywords: pharmacophore